Conditions and Management Strategies for Mangrove Ecosystems as an Effort to Improve the Economy of Youtefa Bay Coastal Communities, Jayapura City - Oscar Oswald O. Wambrauw; Ilham (Formosa Journal of Science and Technology, 2023)
This study aims to find out Conditions and Management Strategies for Mangrove Ecosystems as an Effort to Improve the Economy of Youtefa Bay Coastal Communities, Jayapura City. The method used is a type of library research. Data were obtained from various literature sources, such as: journals, books, proceedings, online platforms and other sources deemed relevant to the research topic. Data analysis is done through; data reduction, data presentation, data verification, and drawing final conclusions. The findings of this study show that the mangrove forests around Youtefa Bay are still degrading. In addition to environmental pollution, which includes function conversions caused by various development goals. Mangrove management with community involvement can contribute to improving the community's economy and public awareness to maintain its sustainability.